EFEITO DAS LEIS REGULAMENTÁVEIS DA PESCA DO PINTADO NOS PARÂMETROS DA CAPTURA, COMPRIMENTO DE MATURAÇÃO E BIOMASSA - ANJOS, Tamara Aparecida Nogueira dos; SÁFADI, Thelma; MARTINS, Solange Gomes Faria (Brazilian Journal of Biometrics, 2018)
The pressure exerted by the shery on the sh stocks leads to a phenotypic evolution and can change the sustainable yield, for this reason, the shery managers must be careful to propose an appropriate management. The species Pseudoplatystoma corruscans, popularly known as Pintado or Surubim, is one of the main targets for catching freshwater sh in South America. From 1996 to 2013 shing regulations in the Paraguay River Basin (Mato Grosso) went through six changes. This paper aims to evaluate the impact of changes in legislation on the parameters of the catch, maturation length and biomass of the Pintado stock, using time series intervention analysis. The data were obtained through simulation, the model is an adaptation of the Penna model based on the biology and the shing characteristics of Pintado. Changes in sheries legislation affected the catch immediately (abruptly), as in the maturation length and biomass parameters, the intervention effect occurs slowly (gradually).